Pediatric Osteosarcoma: An Updated Review - Taran, Shachi Jain; Taran, Rakesh; Malipatil, Nagraj B (Indian Journal of Medical and Paediatric Oncology, 2017)
Osteosarcoma (OS), the most common type of primary malignant bone tumor, is defined by the presence of malignant mesenchymal cells producing osteoid or immature bone. The peak incidence of the most frequent type of OS, i.e., high-grade central OS, occurs in the second decade of life during the adolescent growth spurt. Most patients suffer from the pain and swelling in the involved region and, usually, seek medical attention. Diagnosis is carried out by conventional radiographs, computed tomography, and magnetic resonance image (MRI). In addition, three-phase bone scans, thallium scintigraphy, dynamic MRI, and positron emission spectroscopy are new innovative promising tools. OS can be treated with surgery, radiotherapy, and chemotherapy. There is a clear need for newer effective agents for patients with OS, especially for patients who afflicted with metastatic and recurrence tumor. Monoclonal antibodies directed against OS may prove useful as treatment, either for drug delivery or for radiopharmaceuticals.
Keywords: Bone tumor; childhood malignancy; musculoskeletal tumor; osteosarcoma; radioresistance